Existence of non-zero solutions for a Dirichlet problem driven by (p(x), q(x)-Laplacian. Issue 15 (13th October 2022) - Chinnì, A.; Sciammetta, A.; Tornatore, E.
ABSTRACT: The paper focuses on a Dirichlet problem driven by the ( p ( x ), q ( x ) ) -Laplacian. The existence of at least two non-zero solutions under suitable conditions on the nonlinear term is established. The approach is based on variational methods.